A calculation of wearproofness and longevity of gradient coverages is at an abrasive wear / P.V. Matviishin, V.A. Gonchar, P.V. Kaplun, V.G. Kaplun // Problems of Tribology. – 2012. – № 1. – Р. 116-119. - Матвіїшин, П.В.; Гончар, В.А.; Каплун, П.В.; Каплун, В.Г. (Problems of Tribology, 2014)
The method of calculation of wearproofness of gradient is developed coverage at an abrasive wear on the example of the nitrided layers.